Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2020)
This issue of KIU Journal of Social Sciences focuses on Development Administration, Social Psychology, Gender Studies, Educational Technology, Business and Entrepreneurship Studies. The first part of the Journal addresses issues in Development Administration such as Leadership Recruitment, International Oil Politics, Waste Management, Conflict Management, Rural Development and Poverty Alleviation. It is argued in one of the papers that modes of leadership recruitment have not been credible, transparent and fair. It is indicated that poor conducts during the electoral process has reinforced poverty at the grassroots level. Hence, poor leadership recruitment has affected anti-poverty programmes instituted to combat high level of poverty at the grassroots level in selected states. The paper recommends that there is an urgent need to ensure the credibility, transparency and fairness of modes of leadership recruitment, especially party primary elections in Nigeria. In addition, the electoral umpire should be strengthened for an improved management of the electoral process. Section two explores the social and cultural factors that influence educational, political and judicial activities in the society. It is revealed in one of the papers that there is a high level of awareness, belief and positive perception of police officers to juju practice in criminalities and crime-fighting. Police officersâ€™ adoption of juju powers as a counterforce to combat juju-using criminals appears to be on the increase while they advocate for the recognition of the potency of juju rituals by the criminal justice system. It is therefore recommended that government and police authorities should recognize, orientate, regulate, and engage juju practice and priests, and maintain sound police-community relations in tackling juju-using criminals suggests that students should be thought measures on how to develop their emotional intelligence both by parents and teachers in school. In the Section on Business and Entrepreneurship Studies, it is revealed that business education can reduce the rising rates of absolute poverty and unemployment in Nigeria to a high extent, but is ineffective to address environmental degradation in Nigeria. Based on these findings, it is recommended amongst others, that Government, non-governmental organizations and stakeholders in the education sector should adequately fund business education programmes for sustainable economic growth and development. Papers in Section Four highlight the importance of technolonogy in teaching and learning. One of the papers reveals that many students are not unaware of the instructional media that can be used to learn. It therefore recommends that students be enlightened on the instructional media that can aid their learning of Mathematics and parents/guardians should be encouraged to provide some basic instructional media.  Papers in the fourth Section are on Gender Studies. One of the papers in this section discovers that survival sex health implications are significant in all tertiary institutions, amongst the health implications are unwanted pregnancy and illegal abortion; the health implications are significant in both public and private tertiary institutions. It therefore recommends, among others, that that campaign against survival sex should be floated by government and nongovernmental organizations through media. The last section is on History and Religious Studies. Attempt is made here to dig out the defining features that distinguish modern science from other disciplines from its historical antecedents. Historical exegesis of the rise of modern science is also carried out drawing out its defining characteristics, from the early Greek philosophers through the medieval era to modern times. It is shown that the defining features of modern science are common place procedures carried out by people in their daily activities but, which, taken together as a research procedure, amount to one of the most powerful tools man has devised to know, to conquer, and to control nature. On the whole, this edition of KIU Journal of Social Sciences contains papers that have information on all aspects of human endeavour. Collaborative and cooperative approaches are offered as best approaches for dealing with matters that lead to the instability of communities, societies, economies, and the environment. The theoretical analyses provide opportunities to operationalize the theories discussed in the articles. The authorsâ€™ teachings and areas of research must have certainly influenced their perspectives on the diagnoses of the matters they have addressed in their articles.